Design, developments, and applications of 5G antennas: a review - Pant, Mohit; Malviya, Leeladhar (International journal of microwave and wireless technologies, 2023)
As the demand for high data rates is increasing day by day, fifth-generation (5G) becomes the leading-edge technology in wireless communications. The main objectives of the 5G communication system are to enhance the data rates (up to 20 Gbps) and capacity, ultra-low latency (1 ms), high reliability, great flexibility, and enhance device to device communication. The mentioned objectives lead to the hunting of the millimeter-wave frequency range which lies from 30 to 300 GHz for 5G wireless communications. To design such high capacity, low latency, and flexible systems, antenna design is one of the crucial parts. In this paper, a survey is presented on various antenna designs with their fabrication on different types of substrates such as Rogers RT/duroid 5880, Rogers RO4003C, Taconic TLY-5, etc., at different 5G frequency bands. The different configurations of antennas that covered antenna arrays, multiple-input multiple-output (MIMO) antennas, phased antennas, and beamforming antennas are discussed in detail with their applications. The design of MIMO antennas in the 5G frequency band occupied less space so mutual coupling reduction techniques are required for maintaining the required gain, efficiency, and isolation. This paper is also focused on the mutual coupling reduction techniques and diversity in MIMO antennas.